The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20900/immunometab20200001
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the Landscape of Adipose Tissue-Specific Macrophages and Their Immunometabolic Signatures during Obesity

Abstract: Obesity is a widespread health condition, which can lead to the development of metabolic disorders, such as type 2 diabetes mellitus, nonalcoholic fatty liver disease and cardiovascular diseases. Obesity is marked by the excessive deposition of fat in adipose tissue sites combined with chronic low-grade inflammation. Within this clinical setting, it is well established that adipose tissue macrophages exhibit prominent roles in regulating inflammation and metabolism. However, aside from these wellestablished ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Macrophages exhibit both organ- and niche-specific gene expression and function 5 , 39 so we asked if these AIF1-mediated effects on MAOA expression in BMMs extended to macrophages in adipose tissues. Compared to controls, RNA extracted from intact tissues had mildly lower Maoa expression levels in BAT and iWAT of Aif1 −/− mice fed with either CD or HFD, while reduced Aldh1/2 was seen only in BAT and iWAT of HFD-fed mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages exhibit both organ- and niche-specific gene expression and function 5 , 39 so we asked if these AIF1-mediated effects on MAOA expression in BMMs extended to macrophages in adipose tissues. Compared to controls, RNA extracted from intact tissues had mildly lower Maoa expression levels in BAT and iWAT of Aif1 −/− mice fed with either CD or HFD, while reduced Aldh1/2 was seen only in BAT and iWAT of HFD-fed mice (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blocking the tra cking of in ammatory monocytes into adipose tissue protected mice from obese-associated in ammation and insulin resistance (Arkan et al, 2005, Weisberg et al, 2006). In addition, recent studies have shown that macrophages in adipose tissue can be divided into many subsets in detail, such as sympathetic neuron-associated macrophages (SAMs), lipid-associated macrophages(LAMs), metabolically activated macrophages (MMe), possessing their own cellular metabolic status and functional characteristics in obesity (Korf et al, 2020). In the aspect of lymphocytes, there were increased amounts of CD4 T cells and CD8 T cells in both abdominal subcutaneous and visceral adipose tissues in obese people, accompanied by increased secretion of in ammatory cytokines such as IL-10 secreted by CD4 T cells (Yang et al, 2010, Winer et al, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in single cell and nuclei RNA sequencing approaches greatly improved our understanding of cellular maladaptation's in AT dysfunction and outdated the historical notion that only two macrophage subpopulations (M1 as pro-inflammatory and M2 as anti-inflammatory macrophages) exist 19,20 . In contrast, AT compromises a plethora of different macrophage subtypes, which flexibly adapt to different metabolic challenges [20][21][22] thereby dictating AT remodelling. Thus, it is essential to unravel weight lossinduced changes in the composition of AT to identify the relevant cell types as well as the intracellular mechanisms and intercellular communications that maintain an obesogenic memory in AT.…”
mentioning
confidence: 99%